The Communicative Power of the “Dharma Review” According to the Principles of Dharma Medicine on the Holistic Health Care of Volunteers of Buddhist Dhamma Medicine with SuanPaNaBoon 1, Mukdahan Province - Thongdee, Siripen; Sangkaew, Buchita (Journal of Dhamma for Life, 2025)
These study objectives to investigate (1) the “Dharma Contemplation Verses” based on the principles of Natural Medicine and their communication process to volunteer practitioners, (2) the approaches adopted by volunteers in applying these verses in their daily lives, and (3) the communicative power of the Dharma Contemplation Verses in influencing the holistic well-being of the volunteers. This qualitative research collected data from both message senders and recipients through in-depth interviews and focus group discussions. The findings reveal that (1) the Dharma Contemplation Verses, synthesized from the Tipitaka by Dr. Jaiphet Klajon (Ajarn Mor Khiao), emphasize liberation from suffering and spiritual well-being. The communication process occurs both in group settings and at an individual level, utilizing key dissemination channels such as printed books (52.5%) and health retreats (17.5%). (2) The application of these verses in daily life helps reduce suffering and enhance well-being, with the most widely applied category being the belief in karma and its consequences. Volunteers actively disseminate these teachings through personal recommendations and online platforms. (3) The communicative power of the Dharma Contemplation Verses on holistic well-being is influenced by four primary factors: the sender (Ajarn Mor Khiao, the originator of the verses), the verses themselves, the communication channels (with onsite health retreats being the most impactful), and the receptivity of the audience, which is shaped by their faith in Natural Medicine principles, adherence to ethical precepts, abstinence from intoxicants and animal products, supportive environments, and consistent engagement with the teachings. The study highlights the effectiveness of the Dharma Contemplation Verses in alleviating suffering and promoting well-being. It is recommended that relevant governmental and private sectors incorporate these teachings into their organizational development strategies and educational curricula to benefit individuals across all demographic groups, including the general public, at-risk populations, and patients.